2018
DOI: 10.29173/cjfy29343
|View full text |Cite
|
Sign up to set email alerts
|

Successful Transition Off Academic Probation: A Qualitative Analysis

Abstract: The aim of this study was to identify factors that contributed to the successful transition off academic probation for undergraduate students at MacEwan University1. Focus groups were conducted with volunteers enrolled in any of the main faculties/schools who had successfully to taking time off from university, changing programs, or personal growth. Students underutilized available support services while on academic probation largely due to feelings of embarrassment and shame. Recommendations for institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Considering the history of academic probation (Held, 1941;May, 1923;Reeder, 1942;Stone, 1922) and previous research (Arcand, & Leblanc, 2011;Barouch, 2016;Duffy, 2010;Giampa, & Symbaluk, 2018;Houle, 2013;Hsieh et al, 2007;Lindo, Sanders, & Oreopoulos, 2010;Mathies, Gardner, & Bauer, 2006;Sage, 2010), the goal of this study was to explore the discourse surrounding academic-probation policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the history of academic probation (Held, 1941;May, 1923;Reeder, 1942;Stone, 1922) and previous research (Arcand, & Leblanc, 2011;Barouch, 2016;Duffy, 2010;Giampa, & Symbaluk, 2018;Houle, 2013;Hsieh et al, 2007;Lindo, Sanders, & Oreopoulos, 2010;Mathies, Gardner, & Bauer, 2006;Sage, 2010), the goal of this study was to explore the discourse surrounding academic-probation policies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed how students were affected during academic probation (Fletcher, & Mansur, 2010;Giampa, & Symbaluk, 2018;Holland, 2005;Sage, 2010). For instance, students referred to being on academic probation as shameful, humiliating, disturbing (Arcand & Leblanc, 2011;Duffy, 2010;Houle, 2013), and affecting their self-esteem, self-concepts, and selfefficacy (Arcand & Leblanc, 2013;Hsieh et al, 2007).…”
mentioning
confidence: 99%
“…Begin with your proposed participants. For example, if you are interested in success strategies used by struggling students, you might want to examine views of university students who successfully transitioned off academic probation and you might want to recruit volunteers through invitations sent out via student newsletters (e.g., see Giampa & Symbaluk, 2018). If you were instead conducting a content analysis of gender representation in television programming as depicted above, your proposed unit of analysis might be a random sample of commercials shown on major networks during prime time that contain central characters that are human.…”
Section: Participantsmentioning
confidence: 99%